The Allergic Patient and Advances in Immunology - Tse, Kam (1973)
Our understanding of the basic pathogenetic mechanism of human allergic diseases was made possible by the discovery of IgE and the identification of this immunoglobulin as the key molecule in the mediation of human allergic reactions. The modern immunological principles in connection with the immediate hypersensitivity reaction can be applied to the management of allergic patients in terms of rational approaches in the areas of diagnosis and treatment.